A Cross-Sector Framework to Boost the Sustainable Implementation of Integrated Transport and Spatial Strategies to Improve Safety and Mobility of Moto-Taxi Riders - Mwebesa, Murungi Elizabeth; Chou, Chun-Chen; Yoh, Kento; Doi, Kenji (Frontiers in Sustainable Cities, 2021)
Globally, motorcycle riders make up the biggest percentage of vulnerable road user fatalities. The percentages are higher in African cities where moto-taxi transport is not only the most readily available mode of transport but also a source of income for many especially the youth. Many African cities are re-strategizing on how to sustainably deal with problems like traffic congestion, unplanned development, flooding, air and noise pollution. The authors carried out a questionnaire survey targeting a variety of road safety stakeholders to identify road safety solutions that they think best fit the current situation. Another questionnaire survey targeting moto-taxi riders was carried out, and the data analyzed by SEM to identify how different solutions interact to affect the behavior of riders. Results show that training has the biggest effect on improving behavior of riders as they adapt to new city regulations such as zoning. Other aspects such as presence of customers, behavior of other road users, road environment were also explored. The contribution of this study is a proposal of a combination of solutions that different road safety stakeholders in developing countries can contribute towards the sustainable improvement of the safety of riders, as city authorities look into introducing spatial regulations such as zoning and traffic management strategies such as exclusive lanes